1999
DOI: 10.1111/j.1600-0897.1999.tb00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Susceptibility of the HLA‐DPB1*0402 and HLA‐DPB1*04 Alleles to Unexplained Recurrent Abortion: Analysis by means of Polymerase Chain Reaction–Restricted Fragment Length Polymorphism Method

Abstract: These findings suggest a possible new class II association with patient population of unexplained recurrent abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…[1] Further among the UK RSA patient population linkage disequilibrium between A2 and B12 has been reported. [2] Various studies on HLA DR and DP loci have shown associations with RSA in Italian,[10] Danish,[69] and Japanese[578] populations. Recently, HLA DRB1*1502 has been reported to be significantly associated in Japanese RSA patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Further among the UK RSA patient population linkage disequilibrium between A2 and B12 has been reported. [2] Various studies on HLA DR and DP loci have shown associations with RSA in Italian,[10] Danish,[69] and Japanese[578] populations. Recently, HLA DRB1*1502 has been reported to be significantly associated in Japanese RSA patients.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study on Japanese women documented the positive link between HLA-DPB1*0402 and HLA-DPB1*04 alleles with an increased risk of RPL. 31 This was contradictory to our recent findings on Lebanese women in which DPB1*04:01:01 and DPB1*14:01:01 (and DRB1*07:01:01) were negatively associated with RPL and thus are presumably "RPL-protective 5 ." While these and other findings confirmed a role for the HLA system in the pathogenesis of RPL, they also highlighted the contribution of ethnic/racial background in determining the nature of HLA allele and haplotype associated with altered disease risk, 20,32 including that of RPL.…”
mentioning
confidence: 57%
“…Christiansen et al reported that maternal HLA DR1, DR3, and DR10 were genetic markers for pregnancy loss in Danish recurrent spontaneous abortion patients and their relatives [6]. Our group reported that the frequency of HLA-DPB1*0402 and -DPB1*04 in a patient group with unexplained recurrent abortion was significantly higher compared with healthy fertile women and with the general population [29]. Our group reported that the frequency of HLA-DPB1*0402 and -DPB1*04 in a patient group with unexplained recurrent abortion was significantly higher compared with healthy fertile women and with the general population [29].…”
Section: Discussionmentioning
confidence: 53%